Correlation between texture, earing behaviour and dissolved carbon and nitrogen. Issue 3 (11th February 2017) - Yan, Y.; Kang, Y.; Mo, Z.; Zheng, X.; Shen, Y.
Abstract : The present study compared the differences of texture and earing behaviour in DR tinplate steel sheets. Dissolved carbon and nitrogen contents were discussed as the principal factor. The {001}⟨110⟩ texture component whose earing tendency is higher than that of heterogeneous {111} fibre texture, is harmful for earing property and needed to be reduced to minimum in most cases. The increase of the dissolved carbon and nitrogen contents is responsible for weaker {111} fibre texture and more intense {001}⟨110⟩ component. Additionally, a strong {114}⟨110⟩ texture component was observed on condition of higher dissolved carbon and nitrogen contents and its formation mechanism was discussed.